Managing One's Age in Age-Dissimilar Mentoring Relationships. (April 2023) - Barth, Sara E.; Wessel, Jennifer L.; King, Eden B.; Agrawal, Dewesh
The aging of the workforce creates opportunities for experienced employees to share expertise with newer employees, via mentoring relationships. Age-dissimilar interactions, however, like those between mentor and protégé, can engender challenging interpersonal dynamics such as concern about how others view and respond to them. The current study examines the unique challenges and opportunities of age-dissimilar mentoring relationships, using a sample of doctor and lawyer protégés. Findings suggest that age dissimilarity does not play as large of a role in mentoring relationship outcomes as age-related behaviors. How one manages their age seems to be more important, such that managing one's age in a positive way by redefining age-related stereotypes rather than switching attention away from stereotypes is better for mentoring relationship outcomes no matter the age difference between mentor and protégé. Implications, inferences, and limitations are discussed.